Heavy metals exposure and risk factors for Autism Spectrum Disorder (ASD) among school children in Makassar City, Indonesia - La-Ane, R.; Amqam, H.; Susilawaty, A.; Natsir, M. F.; Yusbud, M.; Adhariana, H. K.; Aris, A. Z. (Elsevier, 2025)
This study investigated the associations between heavy metal exposures and autism spectrum disorder (ASD) in school-aged children from Makassar, Indonesia, using an unmatched case-control design with 30 ASD cases and 30 controls without ASD (aged 6–11 years). Hair samples were analyzed by ICP–MS to quantify mercury (Hg), lead (Pb), and cadmium (Cd) levels. Parental questionnaires collected data on potential confounders, including family income, exclusive breastfeeding, family history of ASD, maternal dietary habits, use of skin-whitening creams, and tobacco smoke exposure. Unconditional logistic regression analysis revealed that children with hair Hg levels below 2.0 µg/g had significantly increased odds of ASD (OR = 19.3; 95 % CI: 1.78–533; p = 0.0312), underscoring a strong association between mercury exposure and ASD risk. Conversely, lower hair Pb levels (< 4.5 µg/g) were linked to reduced odds of ASD (OR = 0.164; 95 % CI: 0.0215–0.980; p = 0.0569), suggesting a contradiction potentially mediated by genetic or epigenetic differences in lead metabolism. Additionally, a positive family history of ASD (OR = 24.7; 95 % CI: 2.20–1195; p = 0.0338) emerged as a robust predictor, while maternal use of skin-whitening creams (OR = 0.119; 95 % CI: 0.0121–0.806; p = 0.0409) and the absence of prenatal tobacco smoke exposure (OR = 9.47; 95 % CI: 1.38–193; p = 0.0494) were significantly associated with ASD risk. These findings highlight the multifactorial etiology of ASD and emphasize that both environmental exposures to heavy metals and specific maternal risk factors substantially influence neurodevelopmental outcomes.